A Hindu Theology of Liberation: Not-Two is Not One, by Anantanand Rambachan - Adluri, Vishwa (Religions of South Asia, 2021)
A Hindu Theology of Liberation: Not-Two is Not One, by Anantanand Rambachan. Albany, NY: State University of New York Press, 2015. xi + 230 pp. £74.94 (hb), £23.50 (pb). ISBN 978-1-4384-5455-9 (hb), ISBN 978-1-4384-5456-6 (pb).